2017
DOI: 10.1002/cmdc.201700619
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of ω‐(Isothiocyanato)alkylphosphinates and Phosphine Oxides as Antiproliferative Agents

Abstract: A series of 21 novel, structurally diverse ω‐(isothiocyanato)alkylphosphinates and phosphine oxides (ITCs) were designed and synthesized in moderate to good yields. The synthesized compounds were evaluated for in vitro antiproliferative activity using LoVo and LoVo/DX cancer cell lines. The biological activity of the synthesized compounds was higher than that of natural isothiocyanates such as benzyl isothiocyanate or sulforaphane. The antiproliferative activity of selected ITCs was also tested on selected can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…During the course of this study, it was also found that phosphinic chlorides are competent coupling partners for aryl iodides creating C−P linkages that are increasingly desired as pharmacophores (Figure A) . Notably, these cross‐coupling conditions are intolerant to water, making them incompatible with traditional DEL formats.…”
Section: Figurementioning
confidence: 99%
“…During the course of this study, it was also found that phosphinic chlorides are competent coupling partners for aryl iodides creating C−P linkages that are increasingly desired as pharmacophores (Figure A) . Notably, these cross‐coupling conditions are intolerant to water, making them incompatible with traditional DEL formats.…”
Section: Figurementioning
confidence: 99%
“…Reaction of phenyl phosphorus halides with potassium thiocyanate can form chemically active phosphorus isothiocyanate in situ . These reagents can react with 2‐imino‐2 H ‐chromene‐3‐carboxamide ( 1 ), forming novel interesting phosphorus‐containing heterocycles.…”
Section: Resultsmentioning
confidence: 99%
“…Isothiocyanateshave many desirable characteristics, including primarily anti-proliferative properties [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Like naturally occurring isothiocyanates (e.g., sulforaphane [ 16 , 17 , 18 , 19 , 20 ] (SFN), phenethyl isothiocyanate [ 21 ] (PEITC), or benzyl isothiocyanate [ 22 ] (BITC)), their synthetically modified analogs with the structure of a phosphorus atom [ 23 , 24 ] or fluorine atom [ 25 , 26 ] also exhibit anti-proliferative activity. Natural as well as synthetic ITCs may additionally have anti-bacterial [ 27 , 28 , 29 , 30 ], anti-fungal [ 31 ], and anti-glioblastoma effects [ 32 ].…”
Section: Introductionmentioning
confidence: 99%